Evaluation of Serious Postmarket Safety Signals Within 2 Years of FDA Approval for New Cancer Drugs. (17th December 2019) - Kim, Janice; Nair, Abhilasha; Keegan, Patricia; Beaver, Julia A.; Kluetz, Paul G.; Pazdur, Richard; Chuk, Meredith; Blumenthal, Gideon M.
Abstract: Background: We examined how often new serious safety signals were identified by the U.S. Food and Drug Administration within the first 2 years after approval for new molecular entities (NMEs) for treatment of cancer that required specific regulatory actions described here. Methods: We identified, for all NMEs approved for treatment of cancer or malignant hematology indications between 2010 and 2016, substantial safety‐related changes within the first 2 years after approval, which included a new Boxed Warning or Warning and Precaution; requirement for (or modification of existing) Risk Evaluation and Mitigation Strategies (REMS); and withdrawal from the market because of safety concerns. Results: Fifty‐five NMEs were approved between 2010 and 2016: 32 (58%) under regular approval (RA) and 23 (42%) under accelerated approval (AA). Of these 55 NMEs, 9 (16%) had substantial safety‐related changes after approval. Across all 55 NMEs, one was temporarily withdrawn from the market for safety reasons (1.8%); one (1.8%) required a new REMS; nine required labeling revisions—new Boxed Warnings were required for two NMEs (3.6%), and new Warnings and Precautions subsections were required for eight (14.6%). One drug (ponatinib) was responsible for several of the substantial safety‐related changes (withdrawal, REMS, Boxed Warnings). One of 32 NMEs approved under RA required a new Warning and Precaution, whereas 7 of 23 NMEs approved under AA had substantial safety‐related changes in the first 2 years after approval. Conclusion: Based on our analysis we conclude that although there was a greater incidence of substantial safety‐related changes to AA drugs versus RA drugs, the majority of these were changes to the Warnings and Precautions and did not substantially alter the benefit‐risk profile of the drug. Implications for Practice: The majority of new cancer drugs (84%) approved in the U.S. do not have new substantial safety information being added to the label within the first 2 years of approval. Unprecedented efficacy seen in contemporary cancer drug development has led to early availability of effective cancer therapies based on large effects in smaller populations. More limited premarket safety data require diligent postmarketing safety surveillance as we continue to learn and update drug labeling throughout the product lifecycle. Abstract : An increasing number of oncology drugs are approved under the FDA Accelerated Approval Program. This article examines new molecular entity approvals and evaluates subsequent changes in recommendations for use of these drugs.